Indonesian Journal of Obstetric and Gynecology (INAJOG) , Vol.4 No.2 Halaman 57-116, April 2016 - Perkumpulan Obstetri Dan Ginekologi Indonesia (POGI, 2016)
- Prevalence of Postpartum Anxiety and Depression after Intrapartum Oxytocin - Profile of Maternal Referrai Cases - A1298C Polymorphism of Fetal Methylenetetrahydrofolate REductase (MTHFR) Gene as a Risk Factor for Spontaneous Abortion - Transforming Growth Factor B1 and Tropoelastin Expression in Uterine Prolapse -...